Promoting Optimal Physical Exercise for Life: An Exercise and Self-Management Program to Encourage Participation in Physical Activity after Discharge from Stroke Rehabilitation—A Feasibility Study. (30th May 2016) - Mansfield, Avril; Knorr, Svetlana; Poon, Vivien; Inness, Elizabeth L.; Middleton, Laura; Biasin, Louis; Brunton, Karen; Howe, Jo-Anne; Brooks, Dina
Abstract : People with stroke do not achieve adequate levels of physical exercise following discharge from rehabilitation. We developed a group exercise and self-management program (PROPEL), delivered during stroke rehabilitation, to promote uptake of physical activity after discharge. This study aimed to establish the feasibility of a larger study to evaluate the effect of this program on participation in self-directed physical activity. Participants with subacute stroke were recruited at discharge from one of three rehabilitation hospitals; one hospital offered the PROPEL program whereas the other two did not (comparison group; COMP). A high proportion (11/16) of eligible PROPEL program participants consented to the study. Fifteen COMP participants were also recruited. Compliance with wearing an accelerometer for 6 weeks continuously and completing physical activity questionnaires was high (>80%), whereas only 34% of daily heart rate data were available. Individuals who completed the PROPEL program seemed to have higher outcome expectations for exercise, fewer barriers to physical activity, and higher participation in physical activity than COMP participants (Hedge's g ≥ 0.5 ). The PROPEL program delivered during stroke rehabilitation shows promise for reducing barriers to exercise and increasing participation in physical activity after discharge. This study supports feasibility of a larger randomized trial to evaluate this program.